Correlation between Calcitonin Levels and [F18]FDG-PET/CT in the Detection of Recurrence in Patients with Sporadic and Hereditary Medullary Thyroid Cancer. (10th May 2012) - Skoura, Evangelia; Datseris, Ioannis E.; Rondogianni, Phivi; Tsagarakis, Stylianos; Tzanela, Marinella; Skilakaki, Maria; Exarhos, Dimitrios; Alevizaki, Maria
Abstract : Purpose . Measurement of serum calcitonin is important in the followup of patients with medullary thyroid carcinoma (MTC) and reliably reflects the presence of the disease. This is the largest study so far in bibliography investigating the diagnostic accuracy of combined [ 18 F]FDG-PET/CT in patients with MTC and elevated calcitonin levels. Methods . Between February 2007 and February 2011, 59 [ 18 F]FDG-PET/CT were performed on 51 patients with MTC and elevated calcitonin levels for localization of recurrent disease. Conventional morphologic imaging methods were negative or showed equivocal findings. Results . Among the 59 [ 18 F]FDG-PET/CT, 29 were positive (26 had true-positive and 3 false-positive findings) and 30 negative. The overall per-patient sensitivity of [ 18 F]FDG-PET/CT was 44.1%. Using as cut-off point the calcitonin value of 1000 pg/ml, in patients with calcitonin exceeding this value, sensitivity raised to 86.7%. The overall sensitivity of [ 18 F]FDG-PET/CT was lower (23%) in patients with MEN IIA syndrome. Conclusion . The findings of this paper show that [ 18 F]FDG-PET/CT is valuable for the detection of recurrence in patients with highly elevated calcitonin levels, >1000 pg/mL, but in patients with lower calcitonin levels, its contribution is questionable. Also, there is evidence that the sensitivity of [ 18 F]FDG-PET/CT is lower in patients with MTC as part of MEN IIA syndrome.